2010
DOI: 10.1128/aem.03136-09
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between Iron Homeostasis and the Osmotic Stress Response in the Halophilic Bacterium Chromohalobacter salexigens

Abstract: In this study, the connection between iron homeostasis and the osmostress response in the halophile Chromohalobacter salexigens was investigated. A decrease in the requirement for both iron and histidine and a lower level of siderophore synthesis were observed at high salinity, and these findings were correlated with a lower protein content in salt-stressed cells. A six-gene operon (cfuABC-fur-hisI-orf6 operon) located downstream of the ectABC ectoine synthesis genes was characterized. A fur strain (in which t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
43
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 77 publications
6
43
1
1
Order By: Relevance
“…A relationship between iron homeostasis and the osmotic stress response has been reported for one bacterium -Chromohalobacter salexigens (Argandoña et al, 2010). The study showed that C. salexigens required less iron at high salt concentrations because cells produced less protein -the assumption being that many proteins contain Fe 3+ at their active site.…”
Section: Energy and Metabolismmentioning
confidence: 95%
“…A relationship between iron homeostasis and the osmotic stress response has been reported for one bacterium -Chromohalobacter salexigens (Argandoña et al, 2010). The study showed that C. salexigens required less iron at high salt concentrations because cells produced less protein -the assumption being that many proteins contain Fe 3+ at their active site.…”
Section: Energy and Metabolismmentioning
confidence: 95%
“…All together, these results suggest that the regime switch is correlated to an internal oxidative stress. The response to iron availability has been linked to the response to osmotic stress in other bacteria (53)(54)(55).…”
Section: Figmentioning
confidence: 99%
“…Cellular extracts used for liquid chromatography-mass spectrometry (LC-MS) and supernatants used for high-pressure liquid chromatography with UV detector (HPLC-UV) analysis of ectoine and hydroxyectoine were prepared by using a modified Bligh-Dyer technique described by Kraegeloh and Kunte (15). For cellular extracts, chromatographic separation and HPLC-electrospray ionization was performed as described by Argandoña et al (16). For supernatants, samples were analyzed as described by García-Estepa et al (2).…”
mentioning
confidence: 99%